Cold at the Core: Osborn Waves in Neurosarcoidosis-Induced Central Hypothermia - Gregory Scott Troutman; Jason Salamon; Matthew Scharf; Jeremy A. Mazurek (Case Reports in Cardiology)
Osborn waves, or J waves, initially described by John Osborn in 1953 in hypothermic dog experiments, are highly sensitive and specific for hypothermia. Initially thought to be secondary to a hypothermia-induced “injury current,” they have more recently been attributed to a voltage differential between epicardial and endocardial potassium (Ito) currents. While the exact conditions required to induce such waves have been debated, numerous clinical scenarios of environmental and iatrogenic hypothermia have been described. Below, we report a novel case of hypothermia—that of neurosarcoidosis-induced central hypothermia with resultant Osborn waves and other associated findings found on electrocardiogram (ECG).